Insecticide spray drift reduction with different adjuvants and spray nozzles1 - Marubayashi, Rodrigo Y. P.; Oliveira, Rone B. de; Ferreira, Marcelo da C. [UNESP]; Roggia, Samuel; Moraes, Eder D. de; Saab, Otavio J. G. A. (Univ Federal Campina Grande, 2021)
: Insecticide spray drift can lead to reduced control efficiency and loss of product to the environment. Thus, we conducted a study to evaluate the effect of different spray nozzles and the addition of adjuvants in insecticide spray on the resulting droplet spectrum and wind tunnel drift. All experiments were conducted in a completely randomized design with four repetitions using a 5 ? 3 factorial scheme. Five spraying solutions were studied; one contained only water and the other four comprised thiamethoxam + lambda-cyhalothrin (no adjuvant, Oro-solve, Wetcit Gold, and Orobor N1), in combination with three spray nozzles (AXI, JFC, and J3D). The droplet spectrum was evaluated through the volumetric median diameter, relative amplitude, and percentage of the droplet volume with diameter <_ 100 ?m. The drifts were evaluated in a wind tunnel at 5, 10, and 15 m. Data were subjected to analysis of variance and means were compared using the Tukey?s test. In addition, a principal component analysis was performed. Application of the insecticide with the adjuvants combined with the different nozzles changed the droplet spectrum and the risk of drift. The AXI nozzle and the J3D associated with the Oro-solve and Wetcit Gold adjuvants resulted in a greater volumetric median diameter of the droplets and drifts were observed at 5 m.
Keywords: application technology; droplet spectrum; wind tunnel